Localization of Nerve Growth Factor Expression to Structurally Damaged Cartilaginous Tissues in Human Lumbar Facet Joint Osteoarthritis - Seidel, Matthias F.; Netzer, Cordula; Chobaz, Véronique; Hügle, Thomas; Geurts, Jeroen (Frontiers in Immunology, 2022)
Purpose Nerve Growth Factor (NGF) is a pivotal mediator of chronic pain and plays a role in bone remodelling. Through its high affinity receptor TrkA, NGF induces substance P (SP) as key downstream mediator of pain and local inflammation. Here we analysed NGF, TrkA and SP tissue distribution in facet joint osteoarthritis (FJOA), a major cause of chronic low back pain. Methods FJOA specimens (n=19) were harvested from patients undergoing intervertebral fusion surgery. Radiologic grading of FJOA and spinal stenosis, followed by immunohistochemistry for NGF, TrkA and SP on consecutive tissue sections, was performed in ten specimens. Explant cultures (n=9) were used to assess secretion of NGF, IL-6, and SP by FJOA osteochondral tissues under basal and inflammatory conditions. Results NGF was predominantly expressed in damaged cartilaginous tissues (80%), occasionally in bone marrow (20%), but not in osteochondral vascular channels. NGF area fraction in cartilage was not associated with the extent of proteoglycan loss or radiologic FJOA severity. Consecutive sections showed that NGF and SP expression was localized at structurally damaged cartilage, in absence of TrkA expression. SP and TrkA were expressed in subchondral bone marrow in both presence and absence of NGF. Low level NGF, but not SP secretion, was detected in four out of eighteen FJOA explants under both basal or inflammatory conditions (n=2 each). Conclusion NGF is associated with SP expression and structural cartilage damage in osteoarthritic facet joints, but not with radiologic disease severity. NGF tissue distribution in FJOA differs from predominant subchondral bone expression reported for knee OA.